Cyber attacks: The war metaphor in computer science - Paiva Guedes e Silva, Gustavo (2023)
This work investigates the role of metaphorical conceptualization in the development of scientific theorizing in Computer Science and, more specifically, in the field of “Cybersecurity”. Based on data retrieved from academic articles published in annals of recognized events in the field of Computing or Engineering, the analysis shows that the conceptual metaphor ILLEGAL COMPUTER COMMUNICATION NETWORK IS WAR predominates in the approach to unauthorized interference in computer communication networks. It is also pointed out that different warlike terms occur, consistently, throughout all texts, reflecting the cognitive process of conceptual blending (FAUCONNIER and TURNER, 2002), as well as the discourse phenomena of metaphoricity (CAMERON, 2003).